2019
DOI: 10.1038/s41598-019-47188-3
|View full text |Cite
|
Sign up to set email alerts
|

First marine cryptotephra in Antarctica found in sediments of the western Ross Sea correlates with englacial tephras and climate records

Abstract: We report the discovery of an important new cryptotephra within marine sediments close to Cape Hallett (northern Victoria Land), in the western Ross Sea, Antarctica. The cryptotephra is fully characterized for its texture, mineralogy and major- and trace-element data obtained on single glass shards. On the basis of geochemical composition, the cryptotephra is unequivocally correlated with the proximal deposits of an explosive eruption of the poorly known Mount Rittmann volcano, situated in northern Victoria La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…This age is consistent with the spike in nssSO 4 2− concentration at a depth of 183.07 m, where traces of volcanic materials (tephra) were visible to the naked eye. Such a tephra layer was already observed and accurately dated in ice [32,47] and marine cores [48] and was recently attributed to the eruption of Mount Rittmann that occurred in 1254, according to Narcisi et al [47], or in 1252 ± 2 according to Lee et al [49]. The complete list of the known volcanoes found in the nssSO 4 2− profile, their location, type, and altitude are reported in Table 1, while the nssSO 4 2− concentration throughout the whole ice core and the volcanic signatures are reported in Figure 2.…”
Section: Ice Core Dating and Peaks Assessmentmentioning
confidence: 60%
“…This age is consistent with the spike in nssSO 4 2− concentration at a depth of 183.07 m, where traces of volcanic materials (tephra) were visible to the naked eye. Such a tephra layer was already observed and accurately dated in ice [32,47] and marine cores [48] and was recently attributed to the eruption of Mount Rittmann that occurred in 1254, according to Narcisi et al [47], or in 1252 ± 2 according to Lee et al [49]. The complete list of the known volcanoes found in the nssSO 4 2− profile, their location, type, and altitude are reported in Table 1, while the nssSO 4 2− concentration throughout the whole ice core and the volcanic signatures are reported in Figure 2.…”
Section: Ice Core Dating and Peaks Assessmentmentioning
confidence: 60%
“…seven half-lives according to Arias-Ortiz et al (2018)) and a tephra layer recently found in the Edisto inlet sediments (Fig. S1 and S5) (Mount Rittmann volcano eruption, (Di Roberto et al, 2019), which has been identified in the Talos Dome core (696 ± 2 yrs BP; ice record) (Narcisi et al, 2012), Taylor Dome core (709 ± 71 yrs BP; ice record) (Hawley et al, 2003) and West Antarctic Ice Sheet (WAIS) Divide cores (687 ± 7 yrs cal BP) (Di Roberto et al, 2019). For our final age-depth model, we used the more precise age assignment derived from the annually-counted portion of the WAIS Divide 2014 chronology.…”
Section: Local Reservoir Effect and Bayesian Age-depth Modelmentioning
confidence: 82%
“…The glass compositions of BC04 cryptotephra match those of the 1254 C.E. (or 1252 ± 2) tephra from Mount Rittmann widespread in the marine sediments from Cape Hallett [31,57] and in the ice records of the entire West Antarctica [58,[68][69][70][71]. BC04 38-39 cryptotephra compositions also match very well with the composition of 11.1 ± 1.4 ka Aviator tephra (AVT tephra) found in the marine sediments of the Aviator Basin ( [60], and again derived from the Mount Rittmann.…”
Section: Cryptotephra: Correlation With Volcanic Sourcementioning
confidence: 55%
“…These can be clearly distinguished from the pyroclastic products of the other volcanic complexes of North Victoria Land namely Mount Melbourne and the Pleiades volcanoes or from the products of the Mt Erebus volcano, which is located further south than the Central Basin. BC04 38-39 cryptotephra shares a geochemical affinity with several marine tephra and cryptotephra layers recently found interbedded in the Holocene-late Pleistocene sediments of the Ross Sea and in ice records [57,60,61]. The glass compositions of BC04 cryptotephra match those of the 1254 C.E.…”
Section: Cryptotephra: Correlation With Volcanic Sourcementioning
confidence: 58%
See 1 more Smart Citation